2023
DOI: 10.4069/kjwhn.2023.08.19
|View full text |Cite
|
Sign up to set email alerts
|

Content and quality of YouTube regarding women’s health: a scoping review

Jin Hyeon Kim,
Hyun Kyoung Kim

Abstract: Purpose: This scoping review investigated the content and quality of YouTube videos on women’s health.Methods: A literature search of the Cochrane Library, PubMed, Embase, CINAHL, ERIC, and RISS databases was performed using the keywords “(‘youtube’/exp OR youtube OR ‘social media’/exp OR ‘social media’ OR ((‘social’/exp OR social) AND (‘media’/exp OR media))) AND (‘female health care’ OR ((‘female’/exp OR female) AND (‘health’/exp OR health) AND (‘care’/exp OR care)))” from February 21 to 27, 2023. Peer-revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(184 reference statements)
0
2
0
Order By: Relevance
“…Vieth et al (2021) found that the internet was the most common source of contraceptive information among German women [29]. Studies, for instance, researched the experiences of birth control on YouTube [30][31][32][33], TikTok [34,35], and Reddit [36]. An analysis of German SNSs' contraception content on You-Tube, Instagram, and TikTok found clear shortcomings in the quality and completeness of information on these sites [37].…”
Section: The Pill and Mainstream Media-a Problematic Relationship?mentioning
confidence: 99%
“…Vieth et al (2021) found that the internet was the most common source of contraceptive information among German women [29]. Studies, for instance, researched the experiences of birth control on YouTube [30][31][32][33], TikTok [34,35], and Reddit [36]. An analysis of German SNSs' contraception content on You-Tube, Instagram, and TikTok found clear shortcomings in the quality and completeness of information on these sites [37].…”
Section: The Pill and Mainstream Media-a Problematic Relationship?mentioning
confidence: 99%
“…This special issue contains evidence of the digital transformation for women’s health, including women with cancer [ 4 ] and older adults [ 5 ], critical appraisal of mobile apps for pregnant women [ 6 ] and women’s health education using YouTube [ 7 ], and presents new challenges to incorporate artificial intelligence into simulation [ 8 ]. However, more evidence regarding interventions and frameworks and/or models that can enhance rigor of digital health-incorporated research is needed.…”
mentioning
confidence: 99%